A Study on The Theme Change in C-E Translation of Chinese Non-Subject Sentences in Political Discourse: --Taking The 2024 Government Work Report As An Example - Duo, Qi (Pacific International Journal, 2024)
The “Theme-Rheme” Theory is a part of the Metafunctions in System-functional linguistics, and the theory has great research value for translation practice and discourse analysis. The special sentence form of the non-subject clause, with its unique structure of missing the subject part but only the predicate part, is characterized by simplicity and conciseness, which is especially common in political discourse. Based on the perspective of the "Theme-Rheme", this study conducts a quantitative and qualitative analysis of the changes in the "Theme" from the original to the English version of the non-subject sentences in the 2024 Government Work Report. The study reveals that the two most frequent changes of the “Theme” in the translation of political literature are adding Unmarked Theme such as "We", "China" and "the government" and changing “Theme” by translating into the passive voice that translates the original theme as the targeted theme or adds a new theme. Chinese non-subject sentences in political literature lack an operator as the subject. English sentences emphasize logic, the subject needs to be added to lead the whole sentence, to make the discourse more compact. To accurately convey the meaning of these sentences in English, they can be translated into passive voice and the subject adjusted as needed. Given the implicit nature of Chinese and the directness of English, the discipline of theme change aids effective communication. The study seeks to derive objective conclusions through detailed data analysis, offering a new perspective on understanding and appreciating the English translation of political and economic texts.